THE STUDY OF TEMPERATURE EFFECT ON CONVENTIONAL AND MULTISTAGE TRIAXIAL TEST ON ANDESITE AND LIMESTONE - M PURBA (NIM : 121 06 064); Pembimbing : Dr.Ir. Suseno Kramadibrata, RUDI
The strength and behavior of rock is a very important parameter in the design of a mine, both open pit and underground mines. The strength and behavior of rock on force or the load is highly dependent on the conditions of these rocks. Rocks in the earth crust will have compression pressure and temperature increase with increasing depth. Triaxial test is a laboratory test that can predict the strength and behavior of rocks by presenting actual field conditions. Increasement of temperature will reduce the strength of rock and affect rock specimens' process of deformation in triaxial test. Increasement of compression pressure and temperature can cause transition from brittle fracture behaviour of rocks become ductile failure. In this study, triaxial tests were conducted conventionally and multistage on andesite and limestone which the temperature has been increased to 80˚C. Triaxial tests were combined with the ultrasonic wave velocity tests, where the wave velocity data were used as a decisive point of termination. The results showed that the increase in rock temperature to 80˚C has lower the rock strength and increased the ductility of andesite and limestone rocks in triaxial tests. However, the influence of a combination of increasing compression pressure up to 7 MPa and temperature up to 80˚C has not caused any behavioral transition from brittle fracture to ductile failure on andesite and limestone.